2015
DOI: 10.1089/vim.2014.0128
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dendritic Cell–Specific ICAM-3-Grabbing Nonintegrin on Dendritic Cells in the Recognition of Hepatitis B Virus

Abstract: Dendritic cell-specific ICAM-3-grabbing nonintegrin (DC-SIGN) is an essential process for virus infection, such as HIV and hepatitis C, and plays a role in immune escape. However, the role of DC-SIGN in hepatitis B virus (HBV) infection is still unknown. The aim of this study was to investigate the role of DC-SIGN in mediating the maturation and activation of dendritic cells (DCs) when infected by HBV. Highly mannosylated HBV particles were obtained by treating HBV-producing HepG2.2.15 cells with the a-mannosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Moreover, in our previous studies, we found that demannosylation is beneficial to HBV to escape DC-SIGN recognition[10]. Therefore, the upregulation of host α-mannosidases by HBV, as observed in this study, appears to contribute to viral escape[10]. …”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, in our previous studies, we found that demannosylation is beneficial to HBV to escape DC-SIGN recognition[10]. Therefore, the upregulation of host α-mannosidases by HBV, as observed in this study, appears to contribute to viral escape[10]. …”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, while the α-mannosidase I inhibitor kifunensine did not affect the production or secretion of HBV virus particles, it did increase its recognition by DC-SIGN, resulting in activation of the immune response[8,9]. Moreover, in our previous studies, we found that demannosylation is beneficial to HBV to escape DC-SIGN recognition[10]. Therefore, the upregulation of host α-mannosidases by HBV, as observed in this study, appears to contribute to viral escape[10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, production of virions with high-mannose oligosaccharides in the presence of kifunensine resulted in DC-SIGN recognition and binding. More recently, the functional consequence of HBV binding to DC-SIGN was assessed by monitoring the DC maturation and activation when exposed to wild-type and highly mannosylated particles [ 46 ]. The study indicated that a stronger, DC-SIGN dependent immune activation occurs when DCs are stimulated with HBV exposing high-mannose N-linked glycans on the enveloped proteins.…”
Section: Hbv N-glycosylation and The Interaction With The Host Immmentioning
confidence: 99%